1977
DOI: 10.1002/bit.260190303
|View full text |Cite
|
Sign up to set email alerts
|

Aminoacylase pellets

Abstract: Aminoacylase was immobilized on the mycelium pellets of Aspergillus ochraceus by using albumin and glutaraldehyde. No difference in the optimum pH was observed between native aminoacylase and aminoacylase pellets. The aminoacylase pellets were stable in pH 4-8 but they were unstable in alkaline conditions. The aminoacylase pellets were more stable against heavy metal ions and inhibitors than native aminoacylase. However, the degree of the activation of aminoacylase with cobalt ion decreased with the immobiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Use of fungal pellets for immobilization of biomass and enzyme have also been described by Anderson [20]. Pellets of Aspergillus niger species have been used as an effective immobilized enzyme support for glucose oxidase and aminoacylase [21].…”
Section: Introductionmentioning
confidence: 99%
“…Use of fungal pellets for immobilization of biomass and enzyme have also been described by Anderson [20]. Pellets of Aspergillus niger species have been used as an effective immobilized enzyme support for glucose oxidase and aminoacylase [21].…”
Section: Introductionmentioning
confidence: 99%
“…Aminoacylase (EC 3.5.1.14) and D-glucose oxidase (EC 1.1.3.4) have been bound on to mycelial pellets of Aspergillus ochraceus by the co-cross-linking method (Section II,C,l,c), using glutaraldehyde and albumin (Hirano et al, 1977;Karube et aL, 1977c). By using the metal-chelation method (Section II,B,2), glucoamylase (EG 3.2.1.3), α-amylase (EC 3.2.1.1), and a protease have been coupled to titanium(IV)-treated Saccharomyces cerevisiae cells.…”
Section: E Miscellar^eous Methods Of Whole-cell Immobilizationmentioning
confidence: 99%
“…Enzyme leakage from microbial pellets has been observed earlier. Hirano et al (1977) reported leakage of 68% of aminoacylase activity during incubation for 4 days of A. ochraceus pellets at p H 7.0 and 20 ° C in 0.05 M phosphate buffer. In pellets of Mortierella vinacea vat.…”
Section: Repeated Lactose Hydrolysismentioning
confidence: 99%